Enhancing context specificity of Water-Sensitive Urban Design - Geert J.M. van der Meulen (A+BE: Architecture and the Built Environment)
Impacts of the climate crisis and urbanisation hit urban environments around the world. Cities taking the lead in mitigating or adapting to the impacts, inspire or actively encourage other contexts to adopt their approach. Water-Sensitive Urban Design (WSUD) is an urban water management approach seeking integration with urban design to provide principles for minimising the hydrological impact of cities on its surroundings and enclosed natural environment while maximising positive impacts through ecosystem services. Urban design, however, is by definition context-specific and maladaptative outcome ensued from lacking contextualisation of WSUD. By bringing the urban design process to the fore, the research challenges universality of WSUD and positions the need for enhanced context specificity. Indian secondary city case studies are used to test a reconceptualisation of water sensitivity and provide evidence for the importance of diverse context knowledge and the contribution of urban design methods to gather and articulate such information about a unique site. Emphasised urban design in WSUD shifts its focus from water system optimization to inclusion of context characteristics defining how to design and manage water for each urban environment.